Inflammatory Mesenteric Disease and Sarcoidosis-like Reaction in a Patient with Lung Adenocarcinoma Who Received Pembrolizumab: Paraneoplastic Syndrome, Secondary to Checkpoint Inhibitor or Chance Finding? - Luis Posado-Domínguez; María Escribano-Iglesias; Lorena Bellido-Hernández; Johana Gabriela León-Gil; María Asunción Gómez-Muñoz; Felipe Gómez-Caminero López; María Martín-Galache; Sandra M. Inés-Revuelta; Emilio Fonseca-Sánchez (Current Oncology)
Summary: Anti PD1/PD-L1 agents, including pembrolizumab, have revolutionized the oncological treatment of different types of cancer, including non-small cell lung cancer. The most frequent complications associated with this type of treatment are mild and are located at the thyroid, pulmonary or hepatic level. Sarcoid like reaction and mesenteric panniculitis secondary to pembrolizumab treatment are two very rare adverse effects. We present the case of a patient with these complications. Purpose: the treatment of metastatic non-small cell lung cancer has undergone a major change in the last 10 years, largely due to the advent of immunotherapy. Anti PD1 agents such as pembrolizumab have increased the median survival of these patients from 13 to 26 months. Most frequent immunorelated side effects are hypothyroidism, pneumonitis or elevated liver enzymes. However, there are other adverse effects, including sarcoid-like reaction and mesenteric panniculitis, which should be known by the professionals involved in the diagnosis and treatment of this type of patient. We present the case of a 62-year-old man with a history of unresectable and non-irradiable stage IIIB epidermoid lung carcinoma with a PD-L1 expression of 30% in whom pembrolizumab was discontinued after 4 cycles due to immunorelated arthritis. One year later he consulted for severe abdominal pain. A PET-CT scan was performed, showing hilar lymphadenopathy and inflammation of abdominal mesenteric fat. A biopsy of lesions in both areas showed non-necrotizing granulomatous lymphadenitis in hilar adenopathy and patchy fibrosis of mesenteric fat. The picture was classified as sarcoidosis-like reaction and mesenteric panniculitis secondary to pembrolizumab. Anti-PD1 agents cause hyperactivation of the immune system through T-cell proliferation. Sarcoid-like reaction is a very rare complication that can mask progressive tumor disease. Awareness of immunorelated complications by oncologists, internists, and radiologists is important for an appropriate diagnostic approach and targeted test ordering.